Pembentukan Model Penciptaan Pengetahuan (Knowledge Creation) dalam Mendorong Inovasi pada Koperasi Susu di Indonesia: Suatu Studi Konfirmatori - A Sukmawati; M S Maarif; . Marimin; K Mudikdjo; H Hardjomidjojo; N S Indrasti (Faculty of Animal Science, Bogor Agricultural University, 2008)
Many theories highlighted the critical importance of knowledge creation on the long-term success of the organization. However, the scarcity of empirical work on knowledge creation model has limited our understanding of the overall organizational process involved. To overcome this, we attempt a comprehensive analyze of knowledge creation model within the organization, exploring the relationship between innovation, knowledge creation model, problem-solving capability, absorptive capacity, knowledge acquisition and assets. Data of this case study were taken from three dairy cooperations in Java. Analysis was conducted using Structural Equation Modeling (SEM) with Lisrel 8.72. The results revealed that several contributing factors (problem-solving capability, absorptive capacity, knowledge acquisition and assets) had significant effect on innovation. On the other hand, knowledge creation model had no significant effect on innovation in the context of the dairy cooperation in Indonesia. The implication for managers is that by focusing on externalization process in knowledge creation model within the organization. In the pattern of innovations, product innovation is the most important. Key words: innovation, knowledge creation, problem-solving capability, absorptive capacity, dairy cooperation